2016
DOI: 10.1016/j.ijsu.2016.03.043
|View full text |Cite
|
Sign up to set email alerts
|

The effects of enteral immunonutrition in upper gastrointestinal surgery: A systematic review and meta-analysis

Abstract: Overall, our analysis found that IEN decreases wound infection rates and reduces length of stay. It should be recommended as routine nutritional support as part of the Enhanced Recovery after Surgery (ERAS) programmes for upper GI Surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 33 publications
1
48
0
7
Order By: Relevance
“…One meta-analysis that included studies with patients that underwent esophagectomy, gastrectomy and pancreatectomy, demonstrated that patients who received immunonutrition postoperatively, had a significantly lower risk of wound infection and shorter length of hospital stay. No significant effect of immunonutrition on other postoperative morbidities and mortality was noticed [86]. The reduction in hospital stay and/ or in postoperative complications seems to compensate for the higher cost of immunonutrition compared to standard enteral feeding in a cost-effectiveness analysis [87].…”
Section: Esophageal Abnormalitiesmentioning
confidence: 94%
“…One meta-analysis that included studies with patients that underwent esophagectomy, gastrectomy and pancreatectomy, demonstrated that patients who received immunonutrition postoperatively, had a significantly lower risk of wound infection and shorter length of hospital stay. No significant effect of immunonutrition on other postoperative morbidities and mortality was noticed [86]. The reduction in hospital stay and/ or in postoperative complications seems to compensate for the higher cost of immunonutrition compared to standard enteral feeding in a cost-effectiveness analysis [87].…”
Section: Esophageal Abnormalitiesmentioning
confidence: 94%
“…In addition, a meta-analysis found that enteral IN significantly reduces the incidence of postoperative infectious complication and the LOH in patients undergoing major elective surgery for gastrointestinal malignances [12]. To date, a systematic review and meta-analysis by Wong and Aly [15] has demonstrated that enteral IN decreases wound infection rates and reduces LOH, and that it should be recommended as routine nutritional support as part of the Enhanced Recovery after Surgery (ERAS ® ) programs for upper gastrointestinal surgery. However, thus far, trials have been conducted in heterogeneous patient groups [16], hampering the establishment of recommendations for specific patient groups.…”
Section: Immunonutrition In Esophagogastric Cancermentioning
confidence: 99%
“…For patients without obvious malnutrition, like Mr. Maule, there are no compelling data regarding nutritional supplementation, but it is recommended that enhanced enteral nutrition should be provided during chemo- and radiotherapy treatment [5]. Immune-enteral nutrition may be especially beneficial; pre-operative provision of specialized nutritional support with immune-modulating nutrients reportedly results in less post-operative morbidity and is cost-effective for major operations, including esophagectomy [6]. …”
Section: Physician’s Perspectivementioning
confidence: 99%